2021
DOI: 10.1038/s41598-021-90664-y
|View full text |Cite
|
Sign up to set email alerts
|

A risk score for prediction of poor treatment outcomes among tuberculosis patients with diagnosed diabetes mellitus from eastern China

Abstract: Persons living with diabetes (PLWD) with newly diagnosed tuberculosis are at greater risk of poor treatment outcomes. Identifying and prioritizing high-risk subgroups of PLWD and tuberculosis for tuberculosis programs to target has been rarely performed. We investigated risk factors for poor tuberculosis treatment outcomes among PLWD and developed a predictive risk score for tuberculosis control prioritization. Among PLWD diagnosed with tuberculosis, demographic, clinical, and tuberculosis treatment outcome da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Out of 49 studies included in this meta-analysis, nine studies were from India [ 24 , 27 , 30 , 32 , 36 , 44 , 47 , 57 , 58 ], four from South Korea [ 1 , 29 , 31 , 49 ], three from Taiwan [ 7 , 23 , 40 ], two from Ethiopia [ 2 , 50 ], four from Mexico [ 28 , 34 , 42 , 43 ], six from China [ 17 , 51 , 52 , 54–56 ], one from Thailand [ 25 ], two from Malaysia [ 46 , 62 ], two from Nigeria [ 35 , 59 ], two from Brazil [ 37 , 45 ], two from Georgia [ 38 , 41 ] and one each from Indonesia [ 26 ], Canada [ 33 ], Pakistan [ 39 ], London [ 61 ], Armenia [ 48 ], Nepal [ 53 ] and Albania [ 60 ]. Among these, the study design of 23 studies was retrospective cohort, 19 studies were prospective, one study was a cross-sectional study and one study was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 49 studies included in this meta-analysis, nine studies were from India [ 24 , 27 , 30 , 32 , 36 , 44 , 47 , 57 , 58 ], four from South Korea [ 1 , 29 , 31 , 49 ], three from Taiwan [ 7 , 23 , 40 ], two from Ethiopia [ 2 , 50 ], four from Mexico [ 28 , 34 , 42 , 43 ], six from China [ 17 , 51 , 52 , 54–56 ], one from Thailand [ 25 ], two from Malaysia [ 46 , 62 ], two from Nigeria [ 35 , 59 ], two from Brazil [ 37 , 45 ], two from Georgia [ 38 , 41 ] and one each from Indonesia [ 26 ], Canada [ 33 ], Pakistan [ 39 ], London [ 61 ], Armenia [ 48 ], Nepal [ 53 ] and Albania [ 60 ]. Among these, the study design of 23 studies was retrospective cohort, 19 studies were prospective, one study was a cross-sectional study and one study was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…Among the variables selected, prior TB, consumption habits (alcohol, tobacco, or drug use), age (adult and elderly), biological sex, HIV infection, and schooling level were the risk factors that most contributed to an LTFU during TB treatment. Some of these characteristics have been explored and linked to unfavorable TB treatment outcomes through the relationship with poor therapy adherence, LTFU, and treatment discontinuation [ 20 – 27 ]. It is important to highlight that our study identified history of prior TB as the variable with the most significant impact on the model’s ability to predict LTFU.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, a similar score was developed to predict unfavorable anti-TB treatment outcomes in people living with diabetes from China, however using clinical and radiologic data [ 23 ]. Another study from Mexico developed an algorithm to predict mortality, failure, and drug resistance in newly diagnosed TB patients with clinical features and laboratory tests [ 27 ]. In contrast, our score could be applied in patients with or without diabetes, by utilizing only clinical information, without the necessity of laboratory data or radiographic exams.…”
Section: Discussionmentioning
confidence: 99%
“…Among the variables selected, prior TB, consumption habits (alcohol, tobacco, or drug use), age (adult and elderly), biological sex, HIV infection, and schooling level were the risk factors that most contributed to an LTFU during TB treatment. Some of these characteristics have been explored and linked to unfavorable TB treatment outcomes through the relationship with poor therapy adherence, LTFU, and treatment discontinuation[ 11 , 22 – 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, a similar score was developed to predict unfavorable anti-TB treatment outcomes in people living with diabetes from China, however using clinical and radiologic data[ 24 ]. Another study from Mexico developed an algorithm to predict mortality, failure, and drug resistance in newly diagnosed TB patients with clinical features and laboratory tests[ 28 ]. In contrast, our score could be applied in patients with or without diabetes, by utilizing only clinical information, without the necessity of laboratory data or radiographic exams.…”
Section: Discussionmentioning
confidence: 99%